New developments in pathogenicity and virulence of necrotrophs - Oliver, Richard; Solomon, P. (Elsevier, 2010)
It was generally considered that necrotrophic plant pathogenic fungi possessed simplistic pathogenic mechanisms being typically reliant on ‘blasting’ their way through host tissue with a battery of lytic and degradative enzymes. However recent studies have suggested that this is not true and that necrotrophic fungal pathogens can subtly manipulate the host during infection in a manner similar to biotrophic pathogens. For example, it has been demonstrated that the wheat pathogens Stagonospora nodorum and Pyrenophora tritici-repentis secrete small unique proteins (effectors) that are internalised by host cells and interact with the host in a gene-for-gene relationship to initiate disease, albeit in an inverse manner compared to biotrophs. This paper reviews recent developments in necrotrophic fungal pathogenicity throughout a critical period that arguably saw this field come of age.